Breaking Boundaries in Renewable Energy: Portable Bio-Photovoltaic Systems for the IoT Era - Nur, Muhamad Maulana Azimatun; Dellarohita, Shinta Justicia; Syakira, Salsabila Fara (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2024)
Bio-photovoltaic (BPV) technology represents a promising innovation in renewable energy by harnessing photosynthetic microorganisms, such as microalgae and cyanobacteria, to convert solar energy into electricity. This review examines recent advancements in BPV systems, with a focus on portable applications, immobilization techniques, and hybrid system integrations. The study highlights the critical role of advanced materials, such as graphene and carbon nanotubes, in improving electron transfer efficiency and system performance. Additionally, immobilization strategies using natural polysaccharides like sodium alginate and agar are discussed for their contributions to system stability and scalability. Portable BPV systems have emerged as sustainable solutions for decentralized energy needs, including environmental monitoring and IoT-based applications. Despite their potential, challenges remain in optimizing energy output, improving long-term stability, and reducing production costs. Future directions include the integration of nanotechnology, genetic engineering of microorganisms, and hybrid BPV-solar systems to enhance overall efficiency and expand application scope. This review underscores the transformative potential of BPV technology in achieving sustainable energy goals while addressing global challenges in energy access and environmental conservation. With continued innovation and multidisciplinary collaboration, BPV systems could play a vital role in transitioning toward a cleaner and more resilient energy future.Keywords: Bio-Photovoltaic; Microalgae; Renewable Energy; Portable Systems; Hybrid BPV-Solar Systems; Nanotechnology Integration.